“Can anything good come out of Nazareth?” (Jn 1,46). In the Perspective of the Ethical Turn - Tomczak, Patrycja (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
This article undertakes a reflection on selected aspects of biblical ethics. A parallel reading of the Nathanael (Jn 1,43-51) and the Zacchaeus (Lk 19,1-10) pericopes presents the ethical disposition not as a desire of moral self-improvement, but as openness, freedom from prejudice and readiness for changing the existing concept of good (Nathanael undermines tradition, Zacchaeus shares his wealth). Messianic ethics – not focused on cultivating personal virtues but radically relational, social, and secular – seems to inspire very diverse ethical philosophers (from Levinas or Bonhoeffer to Badiou), and its present-day form is political concern for responsibilization of the global market.